Exploring diabesity pathophysiology through proteomic analysis using Caenorhabditis elegans - Subhadra, Malaimegu; Mir, Dilawar Ahmad; Ankita, Koley; Sindunathy, Muthukrishnan; Kishore, Hambram David; Ravichandiran, Velayutham; Balamurugan, Krishnaswamy (Frontiers in Endocrinology, 2024)
Diabesity, characterized by obesity-driven Type 2 diabetes mellitus (T2DM), arises from intricate genetic and environmental interplays that induce various metabolic disorders. The systemic lipid and glucose homeostasis is controlled by an intricate cross-talk of internal glucose/insulin and fatty acid molecules to maintain a steady state of internal environment.In this study, Caenorhabditis elegans were maintained to achieve glucose concentrations resembling the hyperglycemic conditions in diabetic patients to delve into the mechanistic foundations of diabesity. Worms raised on diets high in glucose and cholesterol exhibited notably increased intracellular triglyceride levels, a decrease in both mean and maximum lifespan, and reduced pharyngeal pumping. The diabesity condition induced oxidative stress, evident from heightened ROS levels and distinct FT-IR spectroscopy patterns revealing lipid and protein alterations. Furthermore, impaired dopamine signalling and diminished locomotors behaviour in diabesity-afflicted worms correlated with reduced motility.Through proteomic analysis, differentially regulated proteins encompassing dysregulated KEGG pathways included insulin signalling, Alzheimer's disease, and nicotinic acetylcholine receptor signalling pathways were observed. Moreover, diabesity led to decreased collagen production, resulting in anatomical disruptions validated through microscopy and immunofluorescence staining. This underscores the impact of diabesity on cellular components and structural integrity in C. elegans, providing insights into diabesityassociated mechanisms.